Group 4 Organometallics Supported by Sterically Hindered β‐Diketonates. Issue 20 (13th May 2020) - Hopkins, Emily J.; Krajewski, Sebastian M.; Crossman, Aaron S.; Maharaj, Franklin D. R.; Schwanz, Logan T.; Marshak, Michael P.
Abstract : The synthesis, characterization, and reactivity of group 4 organometallics supported by β ‐diketonates is reported. Sterically hindered β ‐diketonates, such as 2, 6‐dimesitylbenzoyl pinacolone (L 1 ) and 2, 6‐dimesitylbenzoyl acetylmesitylene (L 2 ), preclude the formation of tetrakis‐ and tris‐chelates, halting at cis ‐octahedrally coordinated M(L n )2 Cl2 (M = Ti, Zr, Hf; L n = L 1, L 2 ). Metathesis with benzylmagnesium chloride affords M(L n )2 Bn2 (M = Zr, Hf) and the reduced Ti(L 1 )2 Bn(THF) species. These are the first structurally‐characterized metal alkyl complexes exclusively supported by β ‐diketonates among the group 4 metals. Thermolysis of Zr(L n )2 Bn2 complexes results in unimolecular migratory insertion reaction, forming an enone by‐product and ZrO2 . Combined Eyring analyses and computational investigations suggest the bond rearrangements are initiated by an initial benzyl migration reaction to the less hindered carbonyl group on the ligand. Activation of M(L n )2 Bn2 (M = Zr, Hf) in the presence of olefins resulted in similar oxygen abstraction. Implications and prospects for β ‐diketonate‐supported catalysis are discussed. Abstract : The synthesis, characterization, and reactivity of group 4 organometallics exclusively supported by β ‐diketonate ligands are reported. Combined crystallography and spectroscopy indicate fluxionality among all ligands involved. Their decomposition pathways and competency in olefin polymerizations are determined. A 1, 3‐benzyl migration is observed for the benzylzirconium(IV) compounds. Implications for first‐row β ‐diketonate‐supported organometallics and catalysis are discussed.